Anxiety, obsession and fear from coronavirus in Indian population: a web-based study using COVID-19 specific scales - Srivastava, Amit; Bala, Renu; Srivastava, Anoop K.; Mishra, Anuj; Shamim, Rafat; Sinha, Prasenjit (International Journal Of Community Medicine And Public Health, 2020)
Background: The mental health and well-being have been severely impacted by the COVID-19 crisis. People are distressed due to the immediate impacts as well as the consequences of physical isolation, which could have lasting effect on overall well-being. The study aimed to assess the psychological effect of the pandemic on the general population of India using COVID-19 specific scales. Method: An online, cross-sectional study was conducted from 20th June 2020 to 4th July 2020 on persons of both sexes and aged 18 years or more. A convenient sampling method was used for recruiting participants. An online Google form was designed and distributed using social media platforms. The psychological effect of the pandemic was assessed using validated scales of coronavirus anxiety scale, obsession with COVID-19 scale, and fear of COVID-19 scale respectively. Result: The study received responses from 2004 participants from 31 states and union territories of India. The overall prevalence of psychological disorder due to COVID-19 was 53.3% (n=1068). The prevalence of anxiety was found to be 3.29% (n=66), obsession 13.47% (270) and fear 46.9% (1045). Around 2.8% (55) of the participants suffered from all three psychological disorders. Pearson correlation test showed a significant positive correlation between all the three psychological morbidities. Conclusions: The study findings showed high prevalence of mental health problems among Indian population during the COVID-19 outbreak with a positive correlation between them.